Improved Optical and Electrochromic Properties of NiOx Films by Low-Temperature Spin-Coating Method Based on NiOx Nanoparticles - Xiaohong Xie (Materials, 2018)
Solution approaches to NiOx films for electrochromic applications are problematic due to the need of an additional high-temperature annealing treatment step in inert gas. In this study, nanostructured NiOx powder with grain size of about 10.1 nm was synthesized for fabrication of NiOx films for electrochromic application. Non-toxic dispersants of isopropanol and deionized water were used and the whole process was carried out in air. The effects of the number of spin-coating layers, annealing temperature, and the volume ratios of isopropanol to deionized water were systematically investigated. Large transmittance change of 62.3% at 550 nm, high coloration efficiency (42.8 cm2/C), rapid switching time (coloring time is 4 s, bleaching time is 3 s), and good stability were achieved in the optimized NiOx film. The optimized process only required a low processing temperature of 150 °C in air with spin-coating three times and 1:2 volume ratio of isopropanol to deionized water. Finally, good cycle durability of up to 2000 cycles without obvious degradation was demonstrated by cyclic voltammetry tests in a LiClO4/propylene carbonate electrolyte. This study provides a simple and effective approach for fabrication of NiOx films at low temperature in air, which is attractive for further commercialization of electrochromic devices.